Microbial Biomass on Particulate Organic Matter in Seawater of the Euphotic Zone - Seki, Humitake (1970)
Microbial biomass on suspended organic matter in seawater of the euphotic zone of Saanich Inlet was investigated. The viable microorganisms were measured by the glucose-uptake method. Microbial carbon on particulate organic matter in seawater was determined to be, on the average, 9.9 μg of C/liter, and there was a regression relationship as y = 0.0062 x − 1.79 with an unbiased variance V(yx)(1/2) = 0.38, where x = particulate organic carbon in seawater (micrograms of C/liter) and y = logarithm of microbial carbon (micrograms of C/liter).